Phytochemical Composition and In Vitro Antioxidant, Anti-Inflammatory, Anticancer, and Enzyme-Inhibitory Activities of Artemisia nilagirica (C.B. Clarke) Pamp - Jawaher J. Albaqami; Tancia P. Benny; Hamida Hamdi; Ammar B. Altemimi; Aswathi Moothakoottil Kuttithodi; Joice Tom Job; Anju Sasidharan; Arunaksharan Narayanankutty (Molecules, 2022)
Plants have been employed in therapeutic applications against various infectious and chronic diseases from ancient times. Various traditional medicines and folk systems have utilized numerous plants and plant products, which act as sources of drug candidates for modern medicine. Artemisia is a genus of the Asteraceae family with more than 500 species; however, many of these species are less explored for their biological efficacy, and several others are lacking scientific explanations for their uses. Artemisia nilagirica is a plant that is widely found in the Western Ghats, Kerala, India and is a prominent member of the genus. In the current study, the phytochemical composition and the antioxidant, enzyme-inhibitory, anti-inflammatory, and anticancer activities were examined. The results indicated that the ethanol extract of A. nilagirica indicated in vitro DPPH scavenging (23.12 ± 1.28 µg/mL), ABTS scavenging (27.44 ± 1.88 µg/mL), H2O2 scavenging (12.92 ± 1.05 µg/mL), and FRAP (5.42 ± 0.19 µg/mL). The anti-inflammatory effect was also noticed in the Raw 264.7 macrophages, where pretreatment with the extract reduced the LPS-stimulated production of cytokines (p < 0.05). A. nilagirica was also efficient in inhibiting the activities of α-amylase (38.42 ± 2.71 µg/mL), α-glucosidase (55.31 ± 2.16 µg/mL), aldose reductase (17.42 ± 0.87 µg/mL), and sorbitol dehydrogenase (29.57 ± 1.46 µg/mL). It also induced significant inhibition of proliferation in breast (MCF7 IC50 = 41.79 ± 1.07, MDAMB231 IC50 = 55.37 ± 2.11µg/mL) and colon (49.57 ± 1.46 µg/mL) cancer cells. The results of the phytochemical screening indicated a higher level of polyphenols and flavonoids in the extract and the LCMS analysis revealed the presence of various bioactive constituents including artemisinin.